2001
DOI: 10.1002/ps.305
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of herbicides in shallow Danish aquifers: an integrated laboratory and field study

Abstract: Degradation of pesticides in aquifers has been evaluated based on a number of co-ordinated field and laboratory studies carried out in Danish aquifers. These studies included investigations of vertical and horizontal variability in degradation rates from the vadose zone to an aquifer, the effects of aerobic versus anaerobic conditions, and the importance of concentration on degradation kinetics for a selected range of herbicides. The studies were based on different experimental approaches ranging from simple b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Thus, sampling from deeper soil horizons and incubating in batch may cause a bias in the results, and the representativeness of the results generated by techniques such as batch experiments, column experiments, and in‐field experiment is an important issue for debate. Some comparison studies have been made (Di et al, 1998; Beulke et al, 2000; Mills et al, 2001; Albrechtsen et al, 2001; Gaus and Casteele, 2004; McDonald et al, 2006) and it is clear that further studies are required to identify and characterize the sources of uncertainty in the output generated by the models (Soulas and Lagacherie, 2001; Dubus et al, 2003; Massey and Lenoir, 2003; Bending et al, 2006). However, a review of the present state of the methodology has identified laboratory dissipation studies as the preferred approach (Soulas and Lagacherie, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sampling from deeper soil horizons and incubating in batch may cause a bias in the results, and the representativeness of the results generated by techniques such as batch experiments, column experiments, and in‐field experiment is an important issue for debate. Some comparison studies have been made (Di et al, 1998; Beulke et al, 2000; Mills et al, 2001; Albrechtsen et al, 2001; Gaus and Casteele, 2004; McDonald et al, 2006) and it is clear that further studies are required to identify and characterize the sources of uncertainty in the output generated by the models (Soulas and Lagacherie, 2001; Dubus et al, 2003; Massey and Lenoir, 2003; Bending et al, 2006). However, a review of the present state of the methodology has identified laboratory dissipation studies as the preferred approach (Soulas and Lagacherie, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Walker et al (2001) found a five-fold variation in degradation rate over a single field with nominally uniform soil characteristics, together with differences in degradation kinetics. In Denmark, Kristensen et al (2001) also observed large variations in rate and extent of mineralization of mecoprop and isoproturon in a chalk aquifer, and Albrechtsen et al (2001) reported substantial spatial variability in herbicide degradation in a range of shallow aquifers. Earlier work by Heron & Christensen (1992) had noted different patterns and rates of mecoprop degradation for groundwater collected from boreholes only 2-10 m apart.…”
Section: Spatial and Temporal Variability Of Pesticide Persistencementioning
confidence: 96%
“…It is only in the past few years that microbial acclimation to herbicides in subsurface aquifer environments has been investigated (1,24,37). Most of these studies involved laboratory incubation and primarily focused on the activity and rate of herbicide degradation.…”
mentioning
confidence: 99%